Impacts of energy star label on energy efficiency in buildings - Ong, Joseph Kai Zheng (Nanyang Technological University, 2019)
Climate change has caused extreme weather events to be experienced around the world. With a goal of sending strong impact on the significance of energy certification toward energy efficiency of buildings worldwide, the value of energy certification is expressed quantitatively against energy consumption. Numerous researchers conducted simulations on energy consumption in buildings. However, simulations mainly focused on the interactions between energy consumption and the surrounding environment of the building, and its impacts remain not completely explored. Therefore, there is a need to further investigate whether energy savings exist substantially on certified buildings and study the effects of physical characteristics of certified buildings on energy savings. Dataset for this research, the 2015 & 2016 Building Energy Benchmarking dataset, were collected from Seattle’s Building Energy Benchmarking and Reporting Program (SMC 22.920). A regression model of 6716 buildings on energy consumption in the City of Seattle is fitted with critical variables like location, time, Energy Star label, building and energy characteristics are considered. Based on the findings, certified buildings have contributed −18.7% energy consumption, which equates to 21.64 kBtu/sf energy savings per year. A random sampling method eliminates the stochastic effects of the extracted dataset in order to look at the quality assurance of regression results with the conditioned dataset. Low rise certified buildings enjoy the highest energy savings of −28.2% among the medium- and high-rise buildings. Similarly, low natural gas intensities with green certification also enjoy greater energy savings by −22.6%.